Perception on postpartum dietary practices among Malay women in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang - Abdul Basir, Siti Munirah; Abdul Rahman, Muhammad Safwan; Mohd Shukri, Nor Azwani; Mohd. Abu Bakar, Wan Azdie (IIUM Press, International Islamic University Malaysia, 2018)
Traditional postpartum practices generally involve food proscriptions and prescriptions. Certain foods are prohibited due to their properties such as “windy”, “cold” and “hot”. As lactating mother needs higher energy and protein intake, this practice may impact their ability to meet their nutritional requirements. Consequently, their health may not be fully restored, wound healing would be slowed, and lactation success may be interfered. This study was conducted in Hospital Tengku Ampuan Afzan (HTAA) to investigate Malay mothers’ perception on confinement dietary practices during postpartum period. A total of 80 respondents aged between 23-43 years old were interviewed using a questionnaire which consisted of an extensive list of food items. It was found that 100% of respondents mentioned that they do observe the traditional postpartum practices after childbirth with most of them (63.0%) chose to confine for up to 44 days. Flavored rice, roti canai and various types of noodle were generally avoided during postpartum period due to their ‘oily/fatty’ property. Tubers, and most fruits and vegetables were also avoided due to their ‘cold’ property. Moreover, the famous ‘reason’ for exclusion of fish was ‘bisa’ and ‘causing itchiness’ for seafood. Milk and dairy products were included in majority of respondents’ diet. Out of 80, 43 (53.8%) respondents avoided soy sauce because it was believed to give negative effect on wound healing. Other than that, iced drink, tea and sugarcane drink were avoided due to their ‘cold’ and ‘sharp/sour’ properties. In addition, statistical tests of all food items show that there is no difference in terms of level of acceptance for each food between women delivered via normal delivery or caesarean section. It is concluded that postpartum food taboo beliefs are still prevalent among Malay women. Extensive food prohibition and restriction causes limited food choices which may affect mothers’ nutritional intake. Thus, a more balanced diet should be recommended for Malay mothers during postpartum period to ensure adequate nutrient intake, as much as culturally acceptable